Degradation of kitchen waste to organic matter subsequently for organic acid production - Aina, Adi Sufian Chan (2025)
A growing population leading to an increasing waste generation has been a global concern. Common methods like landfilling and incineration have limitations, making anaerobic digestion (AD) a safer alternative for managing organic waste. AD is a series of biological processes involving microbial degradation of organic matter in the absence of oxygen. Kitchen waste, which includes discarded food scraps, offers potential beyond biofertilizers or bioplastics, such as producing organic acids. However, the lack of a comprehensive understanding of the efficiency of kitchen waste producing organic acids through anaerobic digestion creates a gap in knowledge, making it difficult to optimize waste management strategies and AD processes for maximum yield and efficiency. This study focuses on the quantification of organic acid production by measuring concentrations and types of organic acid produced from kitchen waste in controlled anaerobic fermentation conditions. Kitchen waste was dried, ground, and fermented with Aspergillus niger for 10 days. The process was monitored using HPLC to identify and measure organic acid concentrations. Through this study, the effect of waste composition on the types and quantities of organic acids produced during anaerobic fermentation was able to be analyzed, which could improve the yield of organic acid. This study proves the potential of degradation of kitchen waste to organic matter, subsequently for organic acid production.